Planning of human resources in education - Ilham Nurjaman; Dede Supriyatna; Dudu Rohman; Badrudin Badrudin; Tanti Fitri Yana (Educenter : Jurnal Ilmiah Pendidikan, 2024)
This study aims to analyze the concept, objectives, functions, and strategic role of human resource planning in educational implementation. This research uses a qualitative approach with a descriptive design through a literature review method. Data were collected from books, scientific journal articles, and relevant policy documents, then analyzed using descriptive qualitative techniques. The results show that human resource planning is a strategic component in educational management that ensures the availability of qualified teaching and educational personnel in accordance with institutional needs. The process includes several interconnected stages, such as needs analysis, organizing, directing, controlling, and evaluation. Effective planning can prevent mismatches between workforce availability and institutional demands, improve personnel professionalism, and enhance the effectiveness of educational management. Furthermore, human resource planning should not be viewed merely as an administrative activity but must be integrated with the vision, mission, and strategic development of educational institutions. Therefore, systematic and long-term oriented human resource planning is essential to improve educational quality and achieve national education goals.